Neighborhood Factors as Predictors of Poor Sleep in the Sueño Ancillary Study of the Hispanic Community Health Study/Study of Latinos - Simonelli, Guido; Dudley, Katherine A.; Weng, Jia; Gallo, Linda C.; Perreira, Krista; Shah, Neomi A.; Alcantara, Carmela; Zee, Phyllis C.; Ramos, Alberto R.; Llabre, Maria M.; Sotres-Alvarez, Daniela; Wang, Rui; et al. (Sleep (New York, N.Y.), 2017)
Abstract Study Objectives: To evaluate whether an adverse neighborhood environment has higher prevalence of poor sleep in a US Hispanic/Latino population. Methods: A cross-sectional analysis was performed in 2156 US Hispanic/Latino participants aged 18–64 years from the Sueño ancillary study of the Hispanic Community Health Study/Study of Latinos (HCHS/SOL). Participants completed surveys of neighborhood environment including perceived safety, violence and noise, the Insomnia Severity Index (ISI), and 7 days of wrist actigraphy. Results: In age and sex-adjusted analyses, short sleep, low sleep efficiency, and late sleep midpoint were all more prevalent among those living in an unsafe neighborhood. After adjustment for background, site, nativity, income, employment, depressive symptoms, and sleep apnea, the absolute risk of sleeping <6 hours was 7.7 (95% CI [0.9, 14.6]) percentage points greater in those living in an unsafe compared to a safe neighborhood. There were no differences in the prevalence of insomnia by level of safety or violence. Insomnia was more prevalent among those living in a noisy neighborhood. In adjusted analysis, the absolute risk of insomnia was 4.4 (95% CI [0.4, 8.4]) percentage points greater in those living in noisy compared to non-noisy neighborhoods. Conclusion: Using validated measures of sleep duration and insomnia, we have demonstrated the existence of a higher prevalence of short sleep and insomnia by adverse neighborhood factors. An adverse neighborhood environment is an established risk factor for a variety of poor health outcomes. Our findings suggest negative effects on sleep may represent one pathway by which neighborhood environment influences health.